2005
DOI: 10.1007/s00384-005-0749-y
|View full text |Cite
|
Sign up to set email alerts
|

Can pathological complete response in the primary tumour following pre-operative pelvic chemoradiotherapy for T3–T4 rectal cancer predict for sterilisation of pelvic lymph nodes, a low risk of local recurrence and the appropriateness of local excision?

Abstract: Pathological complete response in the primary tumour failed to predict a response in the perirectal lymph nodes (p=0.08). The degree of response predicted a lymph node response (p=0.02). The detection of ypCR identified patients with a low rate of pelvic recurrence. This may in the future allow selection of patients for whom local excision can be performed without a higher risk of local relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
64
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(72 citation statements)
references
References 27 publications
6
64
0
1
Order By: Relevance
“…First, because CRT reduces normal lymphocyte levels commensurate with the regression grade of the primary tumor [22,23], the number of lymphocytes in LPNs without metastases may have dropped proportionally to the degree of TRG. Second, the effect of CRT on metastatic lymph nodes in the mesorectum is reportedly correlated with the TRG of the primary tumor [24,25]. Hence, the shrinking effect of CRT on enlarged LPNs, which are potentially metastatic, might be directly correlated with the degree of TRG.…”
Section: Discussionmentioning
confidence: 99%
“…First, because CRT reduces normal lymphocyte levels commensurate with the regression grade of the primary tumor [22,23], the number of lymphocytes in LPNs without metastases may have dropped proportionally to the degree of TRG. Second, the effect of CRT on metastatic lymph nodes in the mesorectum is reportedly correlated with the TRG of the primary tumor [24,25]. Hence, the shrinking effect of CRT on enlarged LPNs, which are potentially metastatic, might be directly correlated with the degree of TRG.…”
Section: Discussionmentioning
confidence: 99%
“…4,16 It is important to state that in some no local recurrences at all were found in groups of pCR patients. 6,17 Nevertheless, regardless of no local recurrences, chance of distant metastases still exists. Primary tumor can completely respond to neoadjuvant therapy, but the problem is distant micrometastatic focuses, which can stay undetected in the time of primary diagnostics.…”
Section: Discussionmentioning
confidence: 99%
“…These patients act similar as group of patients with no response to neoadjuvant therapy. 6,19 There remains an open question why achieving pCR means good prognosis. pCR is achieved in tumors, which themselves have a favourable biological profile with lesser susceptibility to local recurrences or distant metastases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, no significant correlation was found between D8S264 and low histological response scoring (TRG2 and 1; p = 0.67). However, although chemoradiotherapy could induce a complete histological response, some data have shown that relapse is still observed after a complete histological response [21]. In our study, no MS could be linked to downstaging effects after preoperative chemoradiotherapy, but we specified a set of 8 MS alterations that predicted the sensitivity of a tumour to treatment.…”
Section: Discussionmentioning
confidence: 99%